Anti-Atherosclerosis Effect of Angong Niuhuang Pill via Regulating Th17/Treg Immune Balance and Inhibiting Chronic Inflammatory on ApoE-/- Mice Model of Early and Mid-Term Atherosclerosis - Fan, Qinghong; Liu, Yujuan; Rao, Jiaoyu; Zhang, Zhe; Xiao, Wei; Zhu, Tao; Chai, Xiaomeng; Ye, Kaihe; Ning, Na; Yin, Zhen; Chai, Yushuang; Xu, Yimin; et al. (Frontiers in Pharmacology, 2020)
Angong Niuhuang Pill (ANP) is a well-known patent Chinese medicine which is widely used for treating the central nervous system diseases in China for hundreds of years. Atherosclerosis is a multi-factor-induced chronic inflammatory vascular disease. Preventing inflammation is a vital way for treating atherosclerosis in its early stage. In this study, we investigated the protective effects and possible mechanisms of ANP on a high-fat diet induced early and mid-term atherosclerosis ApoE-/- mice. Twelve male C57BL/6J mice were used as the control group, and Sixty male ApoE-/- mice were randomly divided into 5 groups: model group, Simvastatin group, Low-, Medium- and High-dose ANP group and each group was received saline, Simvastatin (3.0mg/kg), Low-dose ANP (0.25 g/kg), Medium-dose ANP (0.50 g/kg), and High-dose ANP (1.0g/kg), respectively, once every other day for 10 weeks. After administration, serum biochemical indices was detected by the automatic biochemical analyzer, the concentrations of IL-6 and IL-10 in the serum was assayed by ELISA, expression levels of IL-1β, TNF-, MMP-2, MMP-9, CCL2 and its receptor CCR2 in the full-length aorta, and expression levels of transcription factors Foxp3, RORγt in the spleen were assayed via western blotting and RT-qPCR. Flow Cytometry was used to analyze Th17 cells and Treg cells. Pathological and histological analysis was completed on aortic root. ANP decreased LDL/HDL ratio, concentrations of IL-6 while increased IL-10 in serum. Moreover, ANP down-regulated the expression levels of IL-1β, TNF-, MMP-2, MMP-9, CCL2 and receptor CCR2 in the full-length aorta. In addition, ANP decreased Th17 cells and expression levels of transcription factor RORγt, increased Treg cells and expression levels of transcription factor Foxp3. ANP improved abnormal pathological conditions of the aorta root and decreased content of collagen fibers and infiltration of inflammatory cells in the aortic root. In conclusion, this study demonstrated that ANP has anti-atherosclerosis effects on a high-fat diet induced ApoE-/- mice early and mid-term AS model via regulating Th17/Treg balance, inhibiting chronic inflammation, reducing plaque collagen fibers, and reducing inflammatory cells infiltration, to exert its multi-channel multi-target anti-early and mid-term AS effects.